(untitled) (City Dental College Journal, 2012)
Objectives: To compare inter-molar width of different classes of dento-alveolar malocclusion in the permanent dentition. Materials and Methods: This study was done at Department of Orthodontics, BSMMU between 1st July 2007 to 1st January 2011. 96 study patient was selected. inter-molar width were measured from dental casts of this Bangladeshi subjects of which 48 male, 48 female, 24 class 1, 24 class 2 div. I, 24 class 2 div. II, 24 class III. A slide calipers with a vernier scale was used to measure the inter-molar width and compared among different malocclusion classes. Results: Intermolar width in maxilla was found maximum in class I malocclusion but Intermolar width in mandible was maximum in class III malocclusion. Least significant difference (LSD) is used to compare two of the four group. P<0.05 was set as the level of significance. Conclusions : Statistically significant difference (p=0.0018) was found when the results is compared among the four malocclusion groups (Table 4). No group showed any significant difference except Class I and Class III, Class II div.1 and Class III, Class II div. 2 and Class III, when compared individually using LSD test (Table 3). DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11831 City Dental College Journal Vol.9(1) 2012 12-14